Pola Bimbingan Religiusitas pada Masa Pandemi di Yayasan Ashabul Yamin Kecamatan Umbulharjo - Lestari, Windi Mega; Husna, Difa’ul; Sutipyo, Sutipyo; Sutarman, Sutarman (Lembaga Yasin AlSys, 2022)
Learning during a pandemic is a serious challenge. To achieve successful learning, it is necessary to have basic values related to religiosity, so that it can become a strong ideology for individuals in facing the challenges of the times. The method used by the author is a qualitative type followed by a descriptive approach. Based on the results of the study, it is known that the religious guidance at the Ashabul Yamin Islamic Study Foundation, Umbulharjo District, Yogyakarta is divided into two programs, namely (a) short-term programs and (b) long-term programs. The short-term program implemented at the Ashabul Yamin Recitation Foundation is rihlah, which is an agenda that is set forth in the form of tadabur nature.